2017
DOI: 10.1177/0020764017748180
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological patterns of mental disorders and stigma in a community household survey in urban slum and rural settings in Kenya

Abstract: More research is needed into the factors explaining the observed differences in opinion about mental illness between the subgroups, and the impact of mental illness on stigma in Kenya in order to create an evidence-based approach against stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Finally, by using the MICA - 4 , we were able to identify negative attitudes towards mental illness and the field of mental health among our sample, which are also common among other non-specialists working in LMICs [ 14 , 19 , 23 – 25 , 27 31 , 33 – 36 ]. While the MICA - 4 has been used in other contexts [ 35 , 36 , 85 90 ], internal consistency and some item-total correlations generated using the sixteen-item scale were poor in our sample.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, by using the MICA - 4 , we were able to identify negative attitudes towards mental illness and the field of mental health among our sample, which are also common among other non-specialists working in LMICs [ 14 , 19 , 23 – 25 , 27 31 , 33 – 36 ]. While the MICA - 4 has been used in other contexts [ 35 , 36 , 85 90 ], internal consistency and some item-total correlations generated using the sixteen-item scale were poor in our sample.…”
Section: Discussionmentioning
confidence: 98%
“…First, non-specialists reported lacking specific knowledge about mental illness and suicide [ 11 – 15 ]. While non-specialists do see people presenting with mental health problems in consultation, the majority are not able to list or recognize symptoms attributable to mental illness [ 16 19 ]. Interestingly, this is also a reality observed with depression and anxiety [ 14 , 20 ], despite these being the most frequently reported and seen mental health problems in non-specialized settings [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be administered by a trained lay person, who reads the questions up to 3 times and records the answers. It has good psychometric properties (Sheehan et al 1997) and has been validated and used in LMICs (Akena et al 2012; Nakimuli-Mpungu et al 2012; van Heyningen et al 2016) including Kenya by the same authors (Mutiso et al 2017). We used it as a confirmatory diagnosis on those participants who were referred on screening positive on mhGAP-IG.…”
Section: Methodsmentioning
confidence: 99%
“…It is hoped that this will lead to more allocation of funds, given the high disability burden caused by mental disorders in particular depression [ 9 ]. For instance, our previous studies found the prevalence of depression in Kenya varies from 18.7% in household surveys [ 10 ] to 42% in populations attending general health facilities [ 11 ]. Up to 96% of cases of depression in populations in general health facilities go unrecognized [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the poor funding for mental health [ 7 ], there are few mental health specialists, lack of awareness on mental disorders and stigma [ 3 , 10 , 12 ], all contributing to the existing large mental health treatment gap, to the extent that most of those in need of mental health services are unable to receive quality care [ 13 ]. In Kenya, health services are devolved to the 47 counties, who then prioritize the services according to their own context and needs while the Ministry of Health at national level gives overall guidance on county polices and technical advice.…”
Section: Introductionmentioning
confidence: 99%